Casing While Drilling - Revolutionizing Drilling Operations for Enhanced Efficiency and Safety - Kumar, Mohit (International Journal of Engineering and Management Research, 2023)
Efficiency and safety are at the core of any field operations in the Oil and Gas industry. During drilling a well, the biggest risk is a stuck pipe incident owing to the wellbore issues. If these issues are not treated timely, they can have devastating effects on the whole drilling operations. Also, running drilling and casing in and out of the borehole poses a huge operational risk on the drilling crew. It is the objective of any well design to minimize safety risks. This paper discusses about a new drilling technology commonly known as Casing While Drilling (CwD) along with factors to design the CwD operations to achieve the desired success.